2015
DOI: 10.1007/s40615-015-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

Minority Use of a National Cancer Institute-Designated Comprehensive Cancer Center and Non-specialty Hospitals in Two Florida Regions

Abstract: Purpose To examine cancer treatment disparities at a National Cancer Institute-designated comprehensive cancer center (NCI-CCC) and non-specialty hospitals. Materials and Methods Florida hospital discharge datasets were used. ICD9-CM codes were used to define patients with female reproductive organ cancers (FROC), male reproductive organ cancers (MROC), and OTHER cancer diagnoses. A total of 7462 NCI-CCC patients and 21,875 non-specialty hospital patients were included in the statistical analysis. Data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…4,17,19 Racial disparities in access to surgical intervention and outcomes are widely documented for African Americans and other minorities in the United States. [1][2][3][4][5][6][7][8][9][10][11][12][13] In the modern era of healthcare reform, efforts such as ACOs and Medical Homes were touted as initiatives that would not only reduce costs and improve care, but also ameliorate disparities in the healthcare system. 16,17,24 However, the mechanisms by which ACOs would impact healthcare disparities, especially when it comes to surgical interventions, were not well described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,17,19 Racial disparities in access to surgical intervention and outcomes are widely documented for African Americans and other minorities in the United States. [1][2][3][4][5][6][7][8][9][10][11][12][13] In the modern era of healthcare reform, efforts such as ACOs and Medical Homes were touted as initiatives that would not only reduce costs and improve care, but also ameliorate disparities in the healthcare system. 16,17,24 However, the mechanisms by which ACOs would impact healthcare disparities, especially when it comes to surgical interventions, were not well described.…”
Section: Discussionmentioning
confidence: 99%
“…(Ann Surg 2019;269:459-464) R acial and ethnic minorities often receive lower quality healthcare than non-Hispanic whites, even after accounting for insurance, socioeconomic status, comorbidities, and patient preferences. [1][2][3][4][5][6][7][8][9][10][11][12][13] This includes reduced access to surgical services. 5 -8,11,12 Skinner et al 5 reported that in the Medicare population African Americans and Hispanics were less likely to receive knee arthroplasty as compared to whites, whereas Sultan et al 13 documented reduced access among African Americans and Hispanic patients at National Cancer Institute-Designated Comprehensive Cancer Centers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When diagnosed with cancer, White men's higher SES and advantage in health-enhancing resources allow them to obtain prompt access to high-quality medical care, more aggressive therapies, and better follow-up monitoring (Aizer et al, 2014;Dolly et al, 2016;Moses et al, 2016;Ziehr et al, 2015). White men with cancer are more likely than minority and female patients to be treated at National Cancer Institute-Designated Comprehensive Cancer Centers, which are at the forefront of innovation and cuttingedge technologies (Sultan et al, 2015). Black patients experience a longer delay from the diagnosis to treatment and also receive fewer procedures to mitigate treatment side effects than White patients (Bustami et al, 2014;Gupta et al, 2016).…”
Section: Social Inequality In Cancer Treatment and Carementioning
confidence: 99%
“…Specialty hospitals often benefit patients in terms of quality, efficiency, and cost of care [14]. However, social disparities can impact which families obtain access to specialty care [15,16]. A literature review found that children with public insurance have poorer access to specialty care than children with private insurance [17].…”
Section: Introductionmentioning
confidence: 99%